2020
DOI: 10.1111/and.13787
|View full text |Cite
|
Sign up to set email alerts
|

The association between acquired premature ejaculation and metabolic syndrome in young Chinese men

Abstract: Premature ejaculation (PE) is one of the most common sexual dysfunctions. The definition, classification, as well as diagnosis of PE have been well investigated over the past (Althof et al., 2010; Laumann, Paik, & Rosen, 1999). The International Society for Sexual Medicine (ISSM) made the definition of PE, including lifelong PE and acquired PE (LPE and APE) as a male sexual dysfunction characterised by ejaculation that always or nearly always occurs prior to or within about one minute of vaginal penetration (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Only when it proved that the adenoma was non-functional, will the patient be recorded in the follow-up list and we selected non-ED subjects from the list as the controls. We think this design is rational not only because some studies in the field of andrology undertake a similar selection method [ 32 , 33 ], but also for the reason that controls in the study were tested strictly to be ED-free subjects before the enrollment. Moreover, there are no literatures showing the link between non-functional adrenal incidentaloma and diet, thus we supposed that currently the control selection was appropriate for the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Only when it proved that the adenoma was non-functional, will the patient be recorded in the follow-up list and we selected non-ED subjects from the list as the controls. We think this design is rational not only because some studies in the field of andrology undertake a similar selection method [ 32 , 33 ], but also for the reason that controls in the study were tested strictly to be ED-free subjects before the enrollment. Moreover, there are no literatures showing the link between non-functional adrenal incidentaloma and diet, thus we supposed that currently the control selection was appropriate for the topic.…”
Section: Discussionmentioning
confidence: 99%
“…The differing prevalence of PE in patients with MetS may be due to the use of different definitions of PE, variations in the number of patients in each study, and the large inconsistency in the prevalence of hyperglycemia in these studies. In a recent study, Lu et al [ 67 ] investigated the relationship between MetS and APE in 500 men with APE and 500 men without APE. They observed that neck circumference, WC, visceral fat ratio, fat mass, FBS, and high sensitivity C-reactive protein (hs-CRP) levels in the APE group were significantly higher than those of the control group.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…They also found that the APE population had a higher prevalence of MetS (35.6% controls vs. 49.4% MetS, p=0.000) and that both the prevalence and severity of PE increased significantly as the number of MetS components increased. In their multivariate analysis, Lu et al [ 67 ] reported that both MetS and hs-CRP are independent risk factors for APE.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…1 . PEDT was used to diagnose PE frequently [ 30 ], which consists of five questions, with a 5-point Likert-type scale, from "not difficult" to “Extremely difficult” accordingly.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used PREQIs to evaluate the impact of various residential environment elements on mental health. We also combined the self-rating Depression Scale (SDS) [ 29 ] and premature ejaculation diagnostic tool (PEDT) [ 30 ] scale to explore the potential impact of residential environment on PE.…”
Section: Introductionmentioning
confidence: 99%